Faktor-faktor yang Berhubungan dengan Inisiasi Menyusu Dini di Wilayah Kepulauan - Wiendra Nicodemus Manongga; Jeannette Irene Christiene Manoppo; Wulan Pingkan Julia Kaunang (Universitas Sam Ratulangi, 2020)
Background: Early Initiation of breastfeeding (EI) is very important in efforts to reduce infant mortality particullarly in islands. The purpose of this study was to analyze the factors associated with EI in the working area of the health center Dapalan kecamatan Tampan’amma kabupaten Kepulauan Talaud. Methode: This study used a quantitative approach to the analytical observational method with a cross sectional study design. This research was conducted in the working area of the Dapalan Public Health Center, Tampan'amma District. This research was conducted in March-May 2020. The population in this study were all mothers who gave birth spontaneously from January to December 2019 as many as 56 mothers. The instrument used in this study was a questionnaire. The data analysis used was bivariate and multivariate analysis. Result: The results showed that the knowledge of mothers with EI has a value of p = 0.001 <from the value of α = 0.05, the motivation of mothers with EI has a value of p = 0.040 <from the value of α = 0.05, family support with EI has p value = 0.938> from the value α = 0.05, the support of health workers with EI has a value of p = 0.000 <from the value of α = 0.05. Of all the variables, support for health workers was the most dominant. Conclusion: That was concluded that the knowledge, motivation and support of health workers are related factors EI.